PENGARUH UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO (DER), RATING BOND DAN MATURITAS TERHADAP YIELD OBLIGASI PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Nuraini Rachmawati, Eka; Veronika Purwanti, Siska (Jurnal Ilmu Manajemen, 2016)
Bonds is one source of funding for both governments and companies that can be obtained from the capital market. The main purpose of the investors in the fund is invested for profit. In profit or yield bonds called yield.Banyak factors affecting yield. This study aimed to examine the effect of firm size, Debt to Equity Ratio (DER), rating and maturity of the banking sector bond yields listed in Indonesia Stock Exchange. The existence of differences in the results of previous studies lead researcher wants to re-examine the factors that affect the yield. The population used in this study is the banking sector bonds recorded during the years 2010-2011 with the title Tbk (Open). The method used in this research is purposive sampling method. Methods of data analysis using multiple regression analysis, using the classical assumption test and test hypotheses in the form of F test and t test. Results of Multiple Regression Analysis is Y = 16 624 - 0,104X1 + 0,073X2 - 0,202X4 0,803X3 + e. The results of this study prove that the size of the company is negative and significant meaning to the bond yield, DER but not significant positive effect on bond yields. Rating significant negative effect on the yield obligasi.Maturitas positive and significant effect on bond yields.